Obstetrics and Gynecology Residents' Perspectives on Wellness: Findings From a National Survey. Issue 3 (March 2019) - Morgan, Helen Kang; Winkel, Abigail Ford; Nguyen, Anh T.; Carson, Sandra; Ogburn, Tony; Woodland, Mark B.
Abstract : OBJECTIVE: To examine U.S. obstetrics and gynecology residents' perceptions of wellness, burnout, and perceived effectiveness of wellness programming. METHODS: In January 2017, a six-item survey was administered at the time of the Council on Resident Education in Obstetrics and Gynecology in-training examination. Respondents voluntarily completed the survey electronically before starting the examination, and responses were anonymous and only linked to postgraduate year. RESULTS: Of the 5, 376 eligible U.S. examinees, 4, 999 (93%) completed the survey, provided residency year status, and were included in the analysis. There was a high prevalence of self-identified wellness problems (burnout 51.2%, depression 32.0%, binge drinking 12.6%, eating disorder 4.7%, drug use 1.1%, and suicide attempt 0.4%). First-year residents were most likely to state that wellness was a priority in their program. The number of residents reporting any problem with wellness increases significantly between the first year (49.8%) and second year (63.7%, P <.001), after which it remains elevated throughout training. Residents who responded that wellness was not a priority in their program were more likely to report wellness issues and burnout ( P <.001). When asked what single intervention all residency programs should provide, 41.2% (2, 059) felt that dedicated time for wellness maintenance was the most important intervention. CONCLUSION: These findings highlight the high prevalence of wellness problems in obstetrics and gynecology residents, and how essential it will be to engage learners in the development of effective, evidence-based interventions. Abstract : This national survey of obstetrics and gynecology residents highlights the prevalence of wellness issues and the importance of engaging trainees in the development of interventions.